Inhibition of Vascular Inflammation by Apolipoprotein A-IV - Shearston, Kate; Tan, Joanne T. M.; Cochran, Blake J.; Rye, Kerry-Anne (Frontiers in Cardiovascular Medicine, 2022)
Background Apolipoprotein (apo) A-IV, the third most abundant apolipoprotein in human high density lipoproteins (HDLs), inhibits intestinal and systemic inflammation. This study asks if apoA-IV also inhibits acute vascular inflammation. Methods Inflammation was induced in New Zealand White rabbits by placing a non-occlusive silastic collar around the common carotid artery. A single 1 mg/kg intravenous infusion of lipid-free apoA-IV or saline (control) was administered to the animals 24 h before collar insertion. The animals were euthanised 24 h post-collar insertion. Human coronary artery cells (HCAECs) were pre-incubated with reconstituted HDLs containing apoA-IV complexed with phosphatidylcholine, (A-IV)rHDLs, then activated by incubation with tumour necrosis factor (TNF)-α. Cell surface vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) in the TNF-α-activated HCAECs was quantified by flow cytometry. VCAM-1, ICAM-1 and 3β-hydroxysteroid-Δ24 reductase (DHCR24) mRNA levels were quantified by real time PCR. Results Apolipoprotein ApoA-IV treatment significantly decreased collar-induced endothelial expression of VCAM-1, ICAM-1 and neutrophil infiltration into the arterial intima by 67.6 ± 9.9% (p < 0.01), 75.4 ± 6.9% (p < 0.01) and 74.4 ± 8.5% (p < 0.05), respectively. It also increased endothelial expression of DHCR24 by 2.6-fold (p < 0.05). Pre-incubation of HCAECs with (A-IV)rHDLs prior to stimulation with TNF-α inhibited VCAM-1 and ICAM-1 protein levels by 62.2 ± 12.1% and 33.7 ± 5.7%, respectively. VCAM-1 and ICAM-1 mRNA levels were decreased by 55.8 ± 7.2% and 49.6 ± 7.9%, respectively, while DHCR24 mRNA expression increased by threefold. Transfection of HCAECs with DHCR24 siRNA attenuated the anti-inflammatory effects of (A-IV)rHDLs. Pre-incubation of TNF-α-activated HCAECs with (A-IV)rHDLs also inhibited nuclear translocation of the p65 subunit of nuclear factor-κB (NF-κB), and decreased IκBα phosphorylation. Conclusion These results indicate that apoA-IV inhibits vascular inflammation in vitro and in vivo by inhibiting NF-κB activation in a DHCR24-dependent manner.